Community supported agriculture’s perceived positive impacts on mental health and vegetable consumption in Norway and the UK - Anna-Birgitte Milford; Daniel Keech; Sarah Wangui Muiruri (Agricultural and Food Economics)
Abstract Community supported agriculture (CSA) is a format for provisioning food, usually vegetables, where consumers are involved, to various degrees, in the production process. In this study of survey data, we explore differences between CSAs in Norway and the UK in terms of organisational models and member characteristics, particularly the factors that contribute to increase member contentment with CSAs, and their perceptions of their own mental health and vegetable consumption. Results show that compared to the British, Norwegian CSA members participate far more actively in the cultivation and harvesting of the vegetables, and more often prepay subscriptions for the whole season. In both countries, CSA membership was perceived to have caused improvements in members’ life quality, vegetable intake and physical and mental health. Members who participated more actively in the CSA and who received more of their vegetables through the CSA, were also more satisfied with their CSA and had a stronger perception that their vegetable consumption level and their mental health were positively affected by membership. Members with lower educational attainment levels were more likely to have discovered new vegetables through the CSA. Environmentally friendly production methods were also found to be important for CSA members. Vegetable quality and affordability were associated with higher contentment, and learning how to cook and grow vegetables through the CSA was associated with higher consumption of, and interest in, new vegetables. Overall, the results indicate that CSAs can stimulate contentment due to their members’ perceptions of social and environmental benefits.